Implementation Of Wearable Radiation Detector - Josephin Arockia Dhivya, A; Chandrasekaran, R; Elsa Joseph, Josline; R.Thamizhvani, T; K.Arun, S; Manoj, V (International Journal of Engineering and Technology, 2018)
Wearable devices are always in race to support and assist the human healthcare. The wearable devices are commonly used to monitor the physiological parameters of the humans and transmitting to the gadgets. In this paper we proposed a novel idea of monitoring the radiation in the environment and alerting the users about the radiation and level of radiation in the environment. In this paper the implementation of a radiation detector based on a semiconductor photodiode. The awareness of the hazardous radiation should be created and the people should aware of the hazardous radiation in the environment. The arduino controller proposedÂ in the prototype acts as the heart of the wearable device. The detected radiation is transmitted through Bluetooth zixbee module and viewed in smart phones.Â Â